2013
DOI: 10.1111/rda.12143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of the GnRH Agonist (Deslorelin) in Dogs Affected by Benign Prostatic Hyperplasia and Evaluation of Prostatic Blood Flow by Doppler Ultrasound

Abstract: In six German Shepherds dogs, GnRH agonist implants (Deslorelin) were inserted subcutaneously one month after histological confirmation of benign prostatic hyperplasia (BPH). Prostatic volume (PV), characteristics of ejaculate, serum testosterone concentrations and Doppler parameters of prostatic and subcapsular arteries were detected at different time intervals, for 6 month. The prostatic volume showed a significantly reduction starting at day 37. The decrease in sperm concentration, motility and increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 39 publications
4
46
0
2
Order By: Relevance
“…There is evidence that the prostatic vascular system is a primary target of androgen action [35] and other evidence suggests that the regression of the prostatic parenchyma in treated dogs occurs secondarily to the regression of the prostatic vascular system through cell death mediated by tissue ischemia/hypoxia [33].…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that the prostatic vascular system is a primary target of androgen action [35] and other evidence suggests that the regression of the prostatic parenchyma in treated dogs occurs secondarily to the regression of the prostatic vascular system through cell death mediated by tissue ischemia/hypoxia [33].…”
Section: Groupmentioning
confidence: 99%
“…In men, the use of Doppler allows for the visualization of neoplastic [27] and hyperplastic changes [28] and for determining prognosis after surgical resection [29,30]. In dogs, the Doppler technique represents a valid noninvasive method for characterizing the blood flow in the prostatic artery in normal dogs [31], benign hyperplasia prostatic-affected dogs [7,32], and treated dogs [33]. The mean RI and PI obtained in the present study for the prostatic artery are similar to those found in the literature [6,7].…”
Section: Groupmentioning
confidence: 99%
“…Recently, colour Doppler blood flow indices indicating dog prostate perfusion after treatment with a 4.7 mg deslorelin implant were described and compared to initial, pre‐treatment values (Polisca et al. ) and values reported for BPH by Günzel‐Apel et al. ().…”
Section: Treatment For Bphmentioning
confidence: 99%
“…Recently, colour Doppler blood flow indices indicating dog prostate perfusion after treatment with a 4.7 mg deslorelin implant were described and compared to initial, pre-treatment values (Polisca et al 2013) and values reported for BPH by G€ unzel-Apel et al (2001). The systolic peak velocity (SPV) and end diastolic velocity (EDV) in prostatic and subcapsular arteries decreased gradually from day 11 after implant administration.…”
Section: Inhibitors Of Steroid Receptorsmentioning
confidence: 99%
“…Это позволяет предполагать, что при андроген-ной недостаточности кровоснабжение ПЖ может ухуд-шаться. Подтверждением этому являются данные, сви-детельствующие, что при ингибировании синтеза тестостерона введением агониста гонадотропин-рили-зинг-гормона деслорелина собакам наряду со снижени-ем его концентрации в крови регистрировали ухудшение кровоснабжения гиперплазированной железы, оцененное допплерографией простатических и субкапсулярных ар-терий и картированием ПЖ [44]. В клиническом иссле-довании О. Б. Жуков и соавт.…”
unclassified